Student Career Maturity: A Study of the Power of Self-Concept and Peer Attachment - Nisa, Yulia Khoerun; Na'imah, Tri; Nur'aeni, Nur'aeni; Herdian, Herdian (Technium Social Sciences Journal, 2023)
This study examines the influence of self-concept and peer attachment on career maturity in Vocational High School "X" students in Ciamis, West Java. The method used is correlational quantitative research. The study population consisted of 576 students, with a sample of 234 students selected using simple random sampling. The data collection instruments used included a career maturity scale (α=0.732) modified from career maturity inventory form c, a self-concept scale (α=0.826) modified from the questionnaire of self-concept 36, and a peer attachment scale (α=0.748) revised from an inventory of parent and peer attachment. Data analysis was performed using multiple linear regression analysis. The results of this study show that self-concept and peer attachment have an essential role in determining the career maturity of Vocational High School students. Partially, it was found that self-concept influenced students' career maturity, while peer attachment did not significantly influence students' career maturity. Nonetheless, it should be noted that social factors remain essential in forming students' career maturity, although they were not considerably proven in this study. Therefore, it is recommended that subsequent researchers investigate other external variables that might affect students' career maturity.